Flexibility-based anti-islanding protection of a microgrid integrated with power grid - Ahmed Mohamed, Ahmed Haidar; Al-Khalid, Othman; Lopes, Luiz A.C. (Institute of Electrical and Electronics Engineers Inc., 2017)
The widespread adoption of Renewable Energy Resources (RER) and Plug-in Electric Vehicles (PEVs) in distribution systems has achieved a substantial energy share, allowing the microgrid to participate in the open market. In fact, the high penetrations of RER and PEVs have increased the importance of impact assessment involving system protection. A framework is presented in this paper for modeling the combined operations of RER based solar Photovoltaic (PV) systems and PEVs in a microgrid integrated with power grid. The paper also proposes a fault current limiter connected in parallel (anti-islanding protection) with the circuit breaker in the point of common coupling (PCC), thus providing current bypass circuit during abnormal conditions. The concept of the proposed scheme is validated under various operating conditions using a 24-hourly dynamic simulation. The results demonstrate the effectiveness of the proposed approach.